IMPLEMENTATION OF EDUCATION ON THE JURISPRUDENCE OF PRAYER AT THE KHAIRUNNISA ISLAMIC STUDY CIRCLE IN MEDAN AMPLAS THROUGH THE STUDY OF THE BOOK KIFAYATUL AKHYAR BY IMAM TAQIYUDDIN ABU BAKAR BIN MUHAMMAD AL-HUSAINI - Bayu Pradana; Hasan Matsum (SOSIOEDUKASI, 2026)
This study aims to analyze the implementation of Islamic jurisprudence (fiqh) learning on prayer practices through the study of classical Islamic texts at Majelis Ta’lim Khairunnisa Medan Amplas. This research employs a qualitative approach with a field research design to explore the learning processes, methods, and their impacts on participants’ religious practices. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that fiqh learning is conducted systematically through the study of Kifayatul Akhyar, integrating both textual and contextual approaches. The learning process combines lecture, demonstration, and discussion methods, which effectively enhance participants’ understanding and practical skills in performing prayer. Demonstration-based learning plays a significant role in bridging the gap between theoretical knowledge and practical application. Furthermore, the use of classical Islamic texts (turats) remains relevant in non-formal education; however, its effectiveness largely depends on the teacher’s ability to contextualize the material. Supporting factors include teacher competence, participants’ enthusiasm, and a conducive religious environment, while inhibiting factors involve limited time, diverse participant backgrounds, and lack of learning media. This study concludes that non-formal Islamic education institutions, such as majelis ta’lim, play a strategic role in improving religious literacy and shaping religious behavior. The study contributes theoretically to Islamic education studies and practically offers insights into developing effective fiqh learning models in non-formal settings.